2013
DOI: 10.1088/1752-7155/7/1/017107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical breath analysis: discriminating between human endogenous compounds and exogenous (environmental) chemical confounders

Abstract: Volatile organic compounds (VOCs) in exhaled breath originate from current or previous environmental exposures (exogenous compounds) and internal metabolic (anabolic and catabolic) production (endogenous compounds). The origins of certain VOCs in breath presumed to be endogenous have been proposed to be useful as preclinical biomarkers of various undiagnosed diseases including lung cancer, breast cancer, and cardio-pulmonary disease. The usual approach is to develop difference algorithms comparing VOC profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 51 publications
4
91
0
Order By: Relevance
“…Environmental volatile compounds can significantly contribute to the body's pool of VOCs through inhalation, ingestion, and percutaneous or mucosal absorption (Miekisch et al 2004, Pleil et al 2013. In agreement with our study, Mochalski et al (2013) found higher concentrations of 2-butanone in room air when compared with exhaled breath, and suggested a contribution of inhaled exogenous 2-butanone to blood levels.…”
Section: Room Airsupporting
confidence: 87%
See 1 more Smart Citation
“…Environmental volatile compounds can significantly contribute to the body's pool of VOCs through inhalation, ingestion, and percutaneous or mucosal absorption (Miekisch et al 2004, Pleil et al 2013. In agreement with our study, Mochalski et al (2013) found higher concentrations of 2-butanone in room air when compared with exhaled breath, and suggested a contribution of inhaled exogenous 2-butanone to blood levels.…”
Section: Room Airsupporting
confidence: 87%
“…Additionally, volatile compounds originating from exogenous sources can be absorbed into the body and thus contribute to the body's pool of VOCs that have been endogenously generated (Miekisch et al 2004, Pleil et al 2013. Thus, clinical studies are often hampered by non-avoidable, host-related, confounding factors that could lead to erroneous conclusions when searching for biomarkers indicating diseases (Filipiak et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The mean respiratory AFs of benzene, toluene, and C8-aromatics from all test subjects were 55.0%, 55.9%, and 66.9%, respectively. The mean respiratory AFs of BTEX in the present study appeared in an order of benzene < toluene < C8-aromatics, the same order as their partition coefficients between blood and air (K B ) [56,100]. No excellent correlation (0.5 < R 2 < 0.6) was observed between body fat rate and the AFs of BTEX.…”
Section: Preliminary Tests Of Real-time Afssupporting
confidence: 41%
“…At steady state, the exhaled/inhaled fractional value (f-value) for benzene has been estimated at 0.17-0.50 and the central compartment (blood) half-life has been estimated at 1.3-3 min. (21,22) Using mean estimates for the f -value and half-life, a 12 ppb exposure to benzene over 3 min would result in an exhaled breath concentration of 0.5 ppb when collected 6 min later (mean collection time). This is < 15% of the mean post-burn breath concentration of benzene (4.2 ppb) we measured.…”
Section: Discussionmentioning
confidence: 99%